AD, Volume 30, n° 4, 2005 - Full Issue - journal system (Africa Development, 2022)
Contents Globalisation and the Challenge of Democracy in Arab North Africa Shahida El-Baz ..................................1 Negotiated Economic Opportunity and Power: Perspectives and Perceptions of Street Vending in Urban Malawi Ignasio Malizani Jimu ...........................35 The State and Labour Control in Malawi: Continuities and Discontinuities Between One-party and Multiparty Systems Lewis B. Dzimbiri ...............................53 Oil Minorities and the Politics of Resource Control in Nigeria Edlyne E. Anugwom ...............................87 Taxation, Migration and the Creation of a Working Class in Kenya Isaac Tarus ..........................................121 Land Tenure Reform under the Economic Liberalisation Regime: Observations from the Tanzanian Experience Masao Yoshida ....................................139 Globalisation and Technology: Problems and Prospects for the Agricultural Sector in Africa Osita Agbu .........................................151 Demise or Resilience, Customary law and the Changing Order in Africa: The Case of chieftaincy in Botswana Wazha G. Morapedi ................................171 Colonialism, Customary Law and the Post-Colonial State in Africa: The Case of Nigeria John Ademola Yakubu .............................201 Autorités traditionnelles, multipartisme et gouvernance démocratique au Cameroun Ibrahim Mouiche ......................................221